Some Aspects of the Principle of Relativity Effects of the Contract in the Light of the Romanian New Civil Code - FIRICĂ, Manuel Cristian (Journal of Advanced Research in Law and Economics, 2016)
The paper addresses the issue of the principle of relativity effects of the contract, a principle effective in the legal system of several countries worldwide. Reviewing some aspects of the principle’s origin, we outlined its quintessence, the manner in which the principle of relativity effects of the contract is reflected in the system of contract law as well as the way it is stipulated in the new Romanian Civil Code, as compared to the old Romanian Civil Code, highlighting the similarities as well as the differences between the two documents.
Keywords: contract, relativity, effects, principle, document, third parties, legal relation, new Civil Code